An Experience Report on User-Centered Chatbot Design through Design Thinking - Ribeiro, Bianca M.; Souza, Kauã H. S.; Silva, Leonardo G.; Villa, João; Vilela, Ricardo F.; Valle, Pedro H. D.; Silva, Williamson (Anais do Workshop sobre Bots na Engenharia de Software (WBOTS); 2025: Anais do II Workshop sobre Bots na Engenharia de Software, 2025)
This paper presents an experience report on the application of Design Thinking to the development of a chatbot designed to facilitate community donations and exchanges. The approach was systematically conducted through the Inspiration, Ideation, and Implementation stages, employing participatory techniques such as interviews, empathy mapping, role storming, and MoSCoW prioritization. The resulting high-fidelity prototype was evaluated by six users, achieving average scores of 5.29 for perceived usefulness and 5.71 for intention to use (TAM), as well as 6.10 for attractiveness (AttrakDiff). Findings indicate that the structured application of Design Thinking supported the creation of interaction flows and features more closely aligned with real user needs, enhancing usability, attractiveness, and empathy in chatbot design. This work offers lessons learned and practical recommendations for teams seeking to adopt user-centered methodologies in conversational interface projects, contributing to the development of more effective and socially relevant solutions.